The Jewish metropolis : New York City from the 17th to the 21st century - Soyer, Daniel (Lands and ages of the Jewish people., 2021)
"The Jewish Metropolis: New York from the 17th to the 21st Century covers the entire sweep of the history of the largest Jewish community of all time. It provides an introduction to many facets of that history, including the ways in which waves of immigration shaped New York's Jewish community; Jewish cultural production in English, Yiddish, Ladino, and German; New York's contribution to the development of American Judaism; Jewish interaction with other ethnic and religious groups; and Jewish participation in the politics and culture of the city as a whole. Each chapter is written by an expert in the field, and includes a bibliography for further reading. The Jewish Metropolis captures the diversity of the Jewish experience in New York"--